Plasma nitric oxide in dogs with pulmonary hypertension secondary or not to left-sided heart disease - Braz, J. B. [UNESP]; Beluque, T. [UNESP]; Ampuero, R. A.N. [UNESP]; Canola, R. A.M. [UNESP]; Batalhão, M. E.; Cárnio, E. C.; Camacho, A. A. [UNESP] (FapUNIFESP (SciELO), 2023)
Nitric oxide (NO) is an important mediator responsible for vasodilation in pulmonary hypertension (PH) in humans. Based on human literature, it is suggested that in dogs there is also NO production decrease in lung tissue in the presence of PH with hypoxia. Therefore, the aim of this research was to determine the indirect plasmatic NO concentration in dogs with PH secondary or not to the left-side heart disease (LHD) and also with low, intermediate and high probability of PH to characterize the NO involvement on PH in dogs. Blood samples were collected from 35 dogs with probability of PH to NO measurement. NO concentration was estimated by the nitrite/nitrate concentration, and it was significantly different (p=0.002) in dogs with PH secondary to LHD (median=14 μM, range 11.19-16.59) and not secondary to LHD (median=25.88μM, range 15.08-36.71). However, this was not significant for the probability of low, intermediate, and high PH, although there was a tendency for NO concentration to be higher in dogs with high PH. The results of this study demonstrate that there is release of NO in dogs with PH, as well as that its dosage could differentiate dogs with PH secondary to LHD from dogs with non-secondary PH
Óxido nítrico plasmático em cães com hipertensão pulmonar secundária ou não à doença cardíaca esquerda
Keywords: hypoxia; nitrate; nitrite; pulmonary arterial pressure; pulmonary vasculature